The elements of exemplary behaviour among excellent lecturers of islamic education in polythechnics / Ahmad Firdaus Mohd Noor, Khairunnisa A Shukor, Ahmad Bakhtiar Jelani, Fathiah Fathil and Khafizatunnisa' Jaapar - Mohd Noor, Ahmad Firdaus; A Shukor, Khairunnisa; Jelani, Ahmad Bakhtiar; Fathil, Fathiah; Jaapar, Khafizatunnisa' (UiTM Cawangan Johor, 2024)
This article discusses the elements of exemplary behaviour among the Islamic Education Lecturers (IELs) in teaching and learning (I'nL) in polytechnics. This study was fully conducted through qualitative method via case study. Six IELs were selected as participants and willing to be interviewed, and the data from the interview were supported by three Heads of Islamic Education Unit, 12 lecturers and 12 students. Then, the data were triangulated with the data obtained through observation and document analysis. This study has used N'Vivo software to generate a pattern of themes and characteristics of the exemplary behaviour in TnL in polytechnics. The result found that there were six elements of exemplary behaviour practised by the IELs in TnL. All elements formed a pattern. That five elements were; reminding people about religion, establishing good relationship, lecturers as role model, avoid slandering and canto/ling lust, observing words and be responsible towards parents and spouses.